Dynamic power supply by hydrogen bound to a liquid organic hydrogen carrier. (15th May 2017) - Fikrt, André; Brehmer, Richard; Milella, Vito-Oronzo; Müller, Karsten; Bösmann, Andreas; Preuster, Patrick; Alt, Nicolas; Schlücker, Eberhard; Wasserscheid, Peter; Arlt, Wolfgang
Graphical abstract: Highlights: Liquid Organic Hydrogen Carrier can store hydrogen in a dense form. Dynamics of hydrogen release are crucial for application in energy storage. Capability of reacting to fast changes in energy demand has been evaluated. The combined system of release and purification unit can react very fast. Abstract: Liquid Organic Hydrogen Carriers (LOHCs) are able to store hydrogen in a dense and safe form at ambient conditions. While storage of electrical energy in these carrier systems is one possible and attractive application, the dynamics of the load profile has been believed to represent a major challenge for this storage technology. Conversely, we report here that storage systems based on the LOHC technology are indeed able to deal with significant variations in power demand. This is due to the significant free volume in the LOHC release unit offering the opportunity to handle dynamic behavior by pressure changes. While pressure changes allow quick adaption of the power release on demand, changes in the reactor temperature lead to slow modification of the power output, as demonstrated in this work for hydrogen release from perhydro-dibenzyltoluene (H18-DBT).